(untitled) (Boletin Médico de Postgrado, 2023)
With the objective of determining the factors that influence the postponement of the delivery of the special degree project of graduate students of the Dean’s Office of Health Sciences of the Universidad Centroccidental Lisandro Alvarado, a study was carried out with a quantitative approach in the form of a cross-sectional descriptive field study whose population consisted of 40 students who met the inclusion criteria. A structured instrument of 32 multiple-choice questions was applied, validated by expert judgment and with a Cronbach’s α reliability of 0.936. The 42.5% of the participants were between 29-30 years old, 70% women, 92.5% Venezuelan, 47.5% single, 55% from the state of Lara and 92.5% with a scholarship. 50% partially agreed on the time to carry out the project; this same percentage recognized weaknesses in the methodological knowledge and difficulty in writing the chapters. Seventy-five percent agree totally with the obligatory nature of the course Research Methodology/Basic Statistics; 40% say that the place to receive counseling is comfortable and adequate, 52.5% refer to difficulties in accessing the internet service, 32.5% do not know the lines of research and 82.5% say that the tutor is trained and updated in the subject of study. It is concluded that there are multiple factors that affect the performance of students in the activities to carry out the PTEG, which are inherent to the student, tutor and the institution.